Bio-Mediated Sandy Soil Stabilization Using Urease Enzymatic Calcite Precipitation: A Sustainable Solution - Srinivasa Reddy V; Hema Latha K; Sudha Lahari Ravulaparthi; Seshagiri Rao M V (E3S Web of Conferences, 2020)
A recently developing bacteria based soil-stabilization technique inspired from microbially impelled calcite precipitation phenomena is verified for geo-technical applications. This phenomena make use of the metabolic mechanics of microorganisms to produce calcite precipitation all through soil matrix enhancing the soil’s engineering properties. Unconfined compressive strength (UCS) and soil hydraulic conductivity or permeability is evaluated to validate the formation of mineral precipitates between and around soil grains. Due to metabolic process of bacteria calcite minerals are generated binding the soil particles together reducing the voids volume and diameter subsequently a dense microstructure is formed. This improvement of soil homogeneity reduces the hydraulic conductivity and increase the unconfined compression strength of bacteria-treated soil samples. From the results of experimental investigations it is confirmed that mineral precipitation biologically proves to be an effective and efficient method of soil stabilization in increasing the stiffness and permeability of soil samples considered for study.